Strategies for preventing end stage kidney disease: the impact of kidney stone disease on CKD in Pakistan - Salman Imtiaz; Ashar Alam (Journal of the Pakistan Medical Association, 2021)
Chronic Kidney Disease (CKD) is one of the major non-communicable diseases that have social and economic impacts along with day-to-day health-related problems. Kidney stone disease is still one of the major causes of CKD in Pakistan. Kidney stone disease is a preventable cause of renal failure, if detected and treated early. Kidney stone is prevalent in the stone belt areas in our country which are located in rural areas. The treatment is very costly, and mostly available only in large cities. The treatment requires tertiary care setup and expertise. Therefore, there is a need to focus on the preventive strategies which are mainly dietary and lifestyle modifications, along with public awareness programmes. Nephrologists and urologists along with the government should take interest and give priority to CKD due to stone disease. Keywords: Pakistan, kidney stones, chronic kidney disease, obstructive nephropathy, stone prevention. Continuous...